The Influence of Classroom Climate, Learning Interest, Learning Discipline and Learning Motivation to Learning Outcomes on Productive Subjects - Jamilah -; Gatot Isnani (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
This study aims to determine: (1) class climate, learning interest, learning discipline, learning motivation, and learning outcomes; (2) the effect of class climate on learning outcomes; (3) the effect of learning interest on learning outcomes; (4) the effect of learning discipline on learning outcomes; (5) the effect of learning motivation on learning outcomes; and (6) the dominant effect between class climate, learning interest, learning discipline, and learning motivation on learning outcomes. The population in this study is a tenth grade student that consist of 175 students, a sample of 120 students with used proportionate random sampling technique. The method used is descriptive analysis and multiple linear regression analysis. The results showed that: (1) class climate can be classified good, learning interest can be classified good, learning discipline can be classified good, learning motivation can be classified good, and learning outcomes can be classified quite high; (2) there is no positive effect and significant between class climate on learning outcomes; (3) there is no positive effect and significant of learning interest on learning outcomes; (4) there is no positive effect and significant of learning discipline on learning outcomes; (5) there is no positive effect and significant of learning motivation on learning outcomes; and (6) learning motivation is the dominant variable affecting learning outcomes.